INVESTIGATION OF ASSESSMENT OF THE ATTITUDE OF STUDENTS TO A HEALTHY LIFESTYLE: The work was supported by the Science Committee of RA, in the frames of the research project № 18T-5C27 - Hovhannisyan, Sahak; Grigoryan, Armen (Modern Psychology, 2024)
The purpose of this article is to present to the professional community the level of knowledge of students about the protection and strengthening of health and their relationship to a healthy lifestyle (HL) determined by the questionnaire survey. This article presents the results of an empirical study conducted to assess students’ attitudes towards a healthy lifestyle. The object of the study was: students’ ideas about the concepts of “health” and “healthy lifestyle”, and their attitude towards these phenomena. The study was conducted using a questionnaire survey, in which 67 students of the Armenian-Russian (Slavic) University took part. The completed questionnaire included 15 questions related to attitudes towards a healthy lifestyle. The questionnaire data were processed by generally accepted methods of mathematical statistics. Based on the above, the article presents the results of a study related to the level of value attitude of young people towards their own health and a healthy lifestyle. The conclusions of this research are related to the determination of the level of value attitude of the young generation to their own health, to a healthy way of life, to physical activity and the main assumptions related to it.